2000
DOI: 10.1002/1097-0045(20000915)45:1<36::aid-pros4>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor gene expression and its relation to the estrogen-inducible HSP27 heat shock protein in hormone refractory prostate cancer

Abstract: BACKGROUND The recent discovery of the classical estrogen receptor α (ERα) in androgen‐insensitive prostate cancer has shed new light on the role of estrogens in endocrine therapy failure. To get more information on downstream events of estrogen signaling in these tumors, we investigated the relation between ERα gene expression, and the estrogen‐inducible heat shock protein HSP27 in recurrent prostatic adenocarcinomas. METHODS Palliative transurethral resection specimens from 50 patients with androgen‐insensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Hsp27 expression is increased in a variety of malignancies, including prostate (6), breast (7), gastric (8), ovarian (9), and bladder cancers (10,11). Furthermore, Hsp27 overexpression has been associated with multidrug resistance (12) and direct inhibition of apoptosis (13,14) and is functionally linked to increased tumorigenicity and treatment resistance in breast (15) and colon (16) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp27 expression is increased in a variety of malignancies, including prostate (6), breast (7), gastric (8), ovarian (9), and bladder cancers (10,11). Furthermore, Hsp27 overexpression has been associated with multidrug resistance (12) and direct inhibition of apoptosis (13,14) and is functionally linked to increased tumorigenicity and treatment resistance in breast (15) and colon (16) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp27 belongs to a family of chaperone proteins that modulate a diverse range of cytoprotective, homeostatic, and pathogenic intracellular activities (13)(14)(15)(16)(17). In neoplasia, Hsps are associated with multidrug resistance (18) and apoptosis (19,20) and are functionally linked to increased tumorigenicity and treatment resistance in breast (21)(22)(23)(24) and colon (25,26) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, short‐term simultaneous treatment (16 wk) of Noble rats with testosterone and estradiol induced intraductal dysplasia in the dorsolateral lobe of the prostate gland, but prolonged treatment (52 wk) resulted in a high incidence of prostatic carcinoma [9]. Various forms of estrogen receptors (ERs) also have been found in prostate cancer cell lines and prostate tumors, including a novel form of ER‐β that is expressed in the epithelial compartment of the prostate [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a vast majority of prostate adenocarcinomas that recur after androgen‐deprivation therapy express the classic ER‐α at the protein and mRNA levels [10]. Furthermore, ER ‐β knockout mice exhibit prostatic hyperplasia [14].…”
Section: Introductionmentioning
confidence: 99%